Kreoling sisters: (un)intimate relationships, child marriages and women spirits. Issue 1 (1st September 2021) - Djeli, Gitan
Abstract : The non-fiction piece, 'kreoling sisters', explores the overlapped histories of slavery and indenture in the Indian Ocean context, Mauritius in particular. It merges memoir writing, indenture studies and Black study and theory to discuss antiblack/antikreol racism and unfreedom during the critical historical time between the beforelife of indenture (that is slavery) and the afterlife of slavery during indenture. 'kreoling sisters' unearths a personal story that touches on the (un)intimacy or unofficialised intimacy between Black mothers and men of Indian descent and their Black-Indo/Kreol children. The aim is to discuss the entanglement between freedom, intimacy, slavery, antiblackness and indenture and disrupt the official, institutional, colonial and patriarchal narratives. The question the piece finally asks is how intimacy and love can exist, with the thought of what freedom could have been in the colony and could be in contemporary times. 'kreoling sisters' wishes to envision how Indenture studies can engage with a Black philosophy of freedom and abolition, that is the abolition of the plantation police, prison and property, inherited from colonialism.